2003
DOI: 10.1108/03090560310495456
|View full text |Cite
|
Sign up to set email alerts
|

Customer repurchase intention

Abstract: This paper develops a general service sector model of repurchase intention from the consumer theory literature. A key contribution of the structural equation model is the incorporation of customer perceptions of equity and value and customer brand preference into an integrated repurchase intention analysis. The model describes the extent to which customer repurchase intention is influenced by seven important factors-service quality, equity and value, customer satisfaction, past loyalty, expected switching cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
320
1
49

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,131 publications
(379 citation statements)
references
References 169 publications
(271 reference statements)
9
320
1
49
Order By: Relevance
“…In addition, Hellier et al [2003] suggested that perceived value is the major factor affecting revisit intention and brand preference. The following hypothesis is formulated:…”
Section: Research Hypotheses and Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Hellier et al [2003] suggested that perceived value is the major factor affecting revisit intention and brand preference. The following hypothesis is formulated:…”
Section: Research Hypotheses and Frameworkmentioning
confidence: 99%
“…Therefore, customers always have many options for their choice, and it is essential for enterprises to increase the value of existing customers and make efforts to attract their repurchasing besides developing new customers [Hanai et al, 2008]. Repurchase intention has been defined as "the individual's judgment about buying again a designated service from the same company, taking into account his or her current situation and likely circumstances" [Hellier et al, 2003]. Rust et al [1995] also suggested that repurchase intentions are consumers' subjective opinions of their behaviour in the future and not always the same as the actual repurchase patterns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Simultaneously marketers also have accepted the significance of creating a clear, unique brand personality (Das et al, 2012;Keller and Richey, 2006) and have taken brand equity as a main compelling factor of consumer preference, usage and purchase intention (Keller, 2003;Romero and Gomez, 2015). It is contended that the higher levels of consumer brand preference is generated due to higher level of brand equity, purchase intentions (Berry, 2000;Chang and Liu, 2009;Senthilnathan and Tharmi, 2012) and repurchase intention (Hellier et al, 2003). Brand equity's competitive advantage is a valuable asset for the firm which owns that particular brand (Motameni and Shahrokhi, 1998).…”
Section: Brand Equitymentioning
confidence: 99%
“…Hellier et al [20] defined the satisfaction as the overall joy or satisfaction felt by customers as the result of service performance to satisfy needs and expectations of customers. The present study defined satisfaction of participants about house wedding events as the outcome perceived before and after experiencing house wedding events.…”
Section: Satisfactionmentioning
confidence: 99%